The strategy of sustainable development and waste management: Case study: Commercial power industry - S. Łęgowik-Świącik (Global Journal of Environmental Science and Management)
In this study, the relationships between two variables: the strategy of sustainable development and the efficiency of waste management in the commercial power industry company have been subjected to discussion. The basis for the explanation of the aforementioned relationships is the assumption that the level of implementation of the strategy of sustainable development is expressed through capital expenditures incurred on the implementation of modern tools of waste management. On the other hand, the efficiency of waste management in the commercial power industry company is reflected by the level of costs incurred on the storage, transport, and sales of this waste. The whole of the presented considerations has been divided into two basic parts, theoretical and empirical. The first part of the paper exposes the strategic dimension of the concept of sustainable development taking into account the economic and environmental efficiency of waste management achieved due to the use of modern management tools. The considerations presented in the second part constitute the response to the research question. The empirical part includes the identification of waste in the commercial power industry company in Poland and the research aiming at the cognition and assessment of relationships between the efficiency of waste management and the implementation of the strategy of sustainable development in the surveyed company. The publication increases the understanding of the coexistence of the strategy of sustainable development and the efficiency of waste management in the company of the commercial power industry operating in Poland, with particular emphasis on waste reduction and the possibility of its redevelopment. The research methods applied to accomplish the objective are literature studies, case study, descriptive analysis, trend analysis, and the Pearson correlation coefficient.